Alcohol‐related suicide across Australia: a geospatial analysis. (7th June 2021) - Hurzeler, Tristan; Buckley, Nicholas A.; Noghrehchi, Firouzeh; Malouf, Peter; Page, Andrew; Schumann, Jennifer L.; Chitty, Kate M.
Abstract: Background : The acute effects of alcohol consumption are a major risk factor for suicide. Positive blood alcohol concentrations are present in almost one‐third of all suicides at time of death. These suicides are defined as alcohol‐related suicides. This cross‐sectional study examines the geospatial distribution/clustering of high proportions of alcohol‐related suicides and reports on socioeconomic and demographic risk factors. Methods : National Coronial Information System (NCIS) data were used to calculate proportions of suicides with alcohol present at the time of death for each level 3 statistical areas (SA3) in Australia. A density analysis and hotspot cluster analysis were used to visualise and establish statistically significant clustering of areas with higher (hotspots) and lower (coldspots) proportions. Subsequently, socioeconomic and demographic risk factors for alcohol use and suicide were reported on for hot and cold spots. Results : Significant clustering of areas with higher proportions of alcohol‐related suicide occurred in northern Western Australia, the Northern Territory and Queensland, as well as inland New South Wales and inland Queensland. Clustering of SA3s with significantly lower proportions occurred in major city and inner regional Sydney and Melbourne. Conclusion and implications for public health : Results from this study identify areas in which prevention strategies should target alcohol use and can be used to inform prevention strategy design. Additionally, hotspots and coldspots identified in this study can be used for further analysis to better understand contextual risk factors for alcohol‐related suicide.